Formulation Design Of Green Tea Chocolate's Product Development Using Integration Of Product Quality And Kano Model In Arafa Tea - Annisaa Rasyida; Yati Rohayati; Atya Nur Aisha (eProceedings of Engineering, 2015)
Abstract Arafa Tea is one of SMEs in Bandung that engaging in tea specialty, with Green Tea Chocolate (GTC) as its excellent product. GTC’s income has the largest contribution in revenue and has the most rapid turnover compared with others. Seeing this opportunity, Arafa Tea intends to expand its developed market by positioning GTC as specialty snack from Bandung. The study was conducted using integration of Product Quality and Kano Model to determine the needs and customer satisfaction of GTC. This study generated true customer needs output that should be improved by Arafa Tea. There are 21 attributes used as customer requirement attributes to measure the performance of GTC and categorized them based on the given satisfaction impact. The result shows ten true customer needs attributes with weak satisfaction value, including three attractive, five must-be and two one-dimensional attributes. All attributes are analyzed and adjusted according Arafa Tea’s ability to obtain the final recommendation of true customer needs. The analysis shows eight true customer needs, including higher intensity cocoa flavor, flavors combination suitability, higher sweetness intensity, attractive green color, lower green tea intensity, clear inclusion of expiration date period, lower bitterness intensity and clear inclusion of attractive brand’s name in packaging. Keywords: customer satisfaction, product quality, kano model